Формування генетико-екосистемної концепції в інтродукційних дослідженнях - Sliusar, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to formate of genetic and ecosystemic conception – system view of process of introduction as a fundamental part of development of populations, biocoenosises, and ecosystems. Material and methods. Object of researches – process (phenomenon) of dispersal of living organisms in biosphere. Subject of researches – process of introduction in relation with processes of anthropogenic and natural dispersal (using the example of plant introduction). We’ve used such methods as literary and analytical, subject and analytical, system and structural, comparative, and theoretical justification. Results. Main terms which indicate on different ways of dispersal of living organisms, have been coordinated. Some mutually causing conceptions and terms have been proved, particularly: “spontaneous anthropogenic dispersal”, “induced anthropogenic dispersal”, “induced anthropogenic migration”, “optimizing introduction”, “induced anthropogenic expansion”, “induced genetic flow”, “cultural and populational system”, and “general populational species system”. Base algorithm of introduction process is proposed. Criterions that indicate on deep relations between all types of dispersal are featured. Modern system definition “introduction of organisms” of is offered. Conclusions. Plant introduction can be considered as: 1) process that determined by economic and scientifical activity of human beings, in other words induced form of anthropochoria, 2) way of interaction between substance, energy, information and ecosystems of modern biosphere, 3) part of global dispersion process (expansion and migration) of living creatures. Role of introduction process in modern biosphere increases depending on anthropogenic transformation of natural ecosystems and formation of artificial ones. Formation of genetic and ecosystemic ideas will promote improvement of plant introduction theory as an instrument of leaded influence of development of ecosystems, biocoenosises, and populations of organisms by means of directed displacement of the substance, energy and information. Further development of proposed conception (in context of ecological and social approach) will help to establish system paradigm of plant introduction, and develop a general theory of organisms’ introduction.